anonymous
  • anonymous
Solve each radical equation by using algebra. Check your solution. I will use sq. rt for square root. 1. sq. rt of (x- 5) = 3 2. sq. rt of ( 2x - 1) = x 3. 3 sq. rt of( x - 2) = 2 sq. rt of( x) 4. sq. rt. of (3x - 2) = x - 2
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
PLEASE HELP THIS IS DUE IN 4 HOURS
anonymous
  • anonymous
1. \[\Large \sqrt{2x-1}=x\] is the first one like this??
anonymous
  • anonymous
second one..

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Thats exactly how its written, exactly how i typed it
anonymous
  • anonymous
but you said you'll use sq.rt for square root, then why did you type sq.rt before equation ? :S ... ? could you draw them please (equations)
anonymous
  • anonymous
1. \[(\sqrt{x-5})^{2}=(3)^2\] x-5=9 x=14
anonymous
  • anonymous
2. \[(\sqrt{2x-1})^{2}=(x)^{2}\] 2x-1=x^2 -x^2+2x-1 --> (solve it with Quadratic quation to find x)
anonymous
  • anonymous
3. \[(3\sqrt{x-2})^{2}=(2\sqrt{x})^{2}\] 9(x-2)=4(x) 9x-18=4x 9x-4x=18 5x=18 x=3.6
anonymous
  • anonymous
4. \[(\sqrt{3x-2})^{2}=(x-2)^{2}\] \[3x-2=x ^{2}-4x+4\] 7x-6=x^2 -x^2+7x-6 -> (solve with quadratic equation)

Looking for something else?

Not the answer you are looking for? Search for more explanations.